CYA securing IIS 6.0 : cover your a** by getting it right the first time - Cheah, Chun Hai.; Schaefer, Ken.; Peiris, Chris (Rockland, MA : Syngress, 2004)
A highly portable, easily digestible road-map to configuring, maintaining and troubleshooting essential IIS 6.0 features. The book is organized around the 15 "MMCs" (Microsoft Management Consoles) that contain the configuration menus for the essential features. The options within each menu are explained clearly, potential problems are identified up-front, and configurations are subsequently presented in the aptly named "By the Book" section for that MMC. Readers will also appreciate the "Reality Check" sidebars througout, which present valuable cost/benefit analyses of situations where there is no single "right" answer. * A checklist for network engineers and administrators to make sure they have configured you network professionally and responsibily * The information needed by networking professionals responsible for configuring, maintaining and troubleshooting Microsoft's Internet Information Server 6.0 * Cleeraly and concisly identifies those features of IIS that represent the highest risk factors for attacks.
Coverage includes: Script Source Access, Information Disclosure, Denial of Service, Buffer Overflows, Directory Traversal, Cross-Site Scripting, Preparing the Operating System, Partitioning Hard Drives, Installing the OS, Preparing the File System, Installing IIS, Installing Hotfixes, Locking Down COM and Database Access, Securing Web Services, Running the IIS Lockdown Wizard, Securing IIS Global Settings, Securing the Default and Administration Web Sites, Disabling Internet Printing, Disabling or Securing the FrontPage Server Extensions, Configuring URLScan, Securing Web Sites, Building a Directory Structure, Setting Master WWW Properties, Securing by Content Type, Authenticating Users, Using Anonymous Authentication, Using Basic Authentication, Using Digest Authentication, Using Integrated Windows Authentication, Using Client Certificate Mapping, Publishing Web Content, Staging and Review, Setting File Attributes, Building File Checksums, Moving Content versus Updating Content, Summary, Solutions Fast Track, Frequently Asked Questions.
Includes index.
Keywords: Microsoft Internet information server; Client/server computing; Computer networks -- Security measures; Electronic mail systems -- Security measures; Electronic books